2013
DOI: 10.1002/lt.23712
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine and tacrolimus have inhibitory effects on toll-like receptor signaling after liver transplantation

Abstract: Toll‐like receptors (TLRs) play a key role in transplantation biology. The effect of immunosuppression on TLR function after liver transplantation is unknown. Peripheral blood mononuclear cells (PBMCs) from 113 post–liver transplant patients and 13 healthy controls were stimulated with TLR‐specific ligands [lipopolysaccharide (TLR4), pan‐3‐cys (P3C) (TLR2), Poly (I:C) (PIC) (TLR3), R848 (TLR7/8), and CpG (TLR9)] for 24 hours. PBMCs from 5 healthy controls were also cultured with therapeutic concentrations of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 28 publications
1
42
0
1
Order By: Relevance
“…The restorative effects of FK506 on fracture healing may also occur through modulation of multiple types of immune cells. Several reports suggest FK506 modulates innate immune cells to generate reduced responses to innate stimuli [3840]. For example, dendritic cells and macrophages pretreated with FK506 were shown to produce lower amounts of pro-inflammatory cytokines after exposure to lipopolysaccharide, a pathogen associated molecular pattern (PAMP) [38, 39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The restorative effects of FK506 on fracture healing may also occur through modulation of multiple types of immune cells. Several reports suggest FK506 modulates innate immune cells to generate reduced responses to innate stimuli [3840]. For example, dendritic cells and macrophages pretreated with FK506 were shown to produce lower amounts of pro-inflammatory cytokines after exposure to lipopolysaccharide, a pathogen associated molecular pattern (PAMP) [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, dendritic cells and macrophages pretreated with FK506 were shown to produce lower amounts of pro-inflammatory cytokines after exposure to lipopolysaccharide, a pathogen associated molecular pattern (PAMP) [38, 39]. PAMPs and damage-associated molecular patterns (DAMPs) both signal through Toll-like receptor (TLR) pathways that are damped in TLR-ligand stimulated peripheral blood mononuclear cells isolated from patients who received FK506 [40]. FK506 also affects the regulatory T (Treg) cell population, which is known to dampen pro-inflammatory immune responses [41].…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer CD56 dim cells from post–liver transplant patients on calcineurin inhibitors also produced less IFN‐γ with TLR7/8 stimulation in comparison with those from healthy controls. Furthermore, these findings were confirmed in healthy human peripheral blood mononuclear cells cocultured with therapeutic concentrations of cyclosporine and stimulated with TLR2, TLR4, and TLR7/8 ligands . These findings are important because they suggest that calcineurin inhibition may further reduce cellular rejection through inhibition of innate immune signaling as well as adaptive immunity.…”
Section: Effect Of Immunosuppression On Toll‐like Receptor Functionmentioning
confidence: 59%
“…Our group recently showed that peripheral blood mononuclear cells from patients on calcineurin inhibitors after liver transplantation had impaired IL‐6 and TNF‐α secretion after ex vivo TLR2, TLR4, and TLR7/8 stimulation in comparison with healthy controls . Natural killer CD56 dim cells from post–liver transplant patients on calcineurin inhibitors also produced less IFN‐γ with TLR7/8 stimulation in comparison with those from healthy controls.…”
Section: Effect Of Immunosuppression On Toll‐like Receptor Functionmentioning
confidence: 99%
See 1 more Smart Citation